2018
DOI: 10.2174/1871520618666180404151218
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of 5-Fluorouracil-loaded Polymer-coated Magnetite Nanographene Oxide Combined with Radiofrequency

Abstract: Therefore, PCL/CHI-SPION-NGO can deliver 5-Fu more efficiently into the CT26 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…These results indicated that the synthesized nanoparticles have imaging capability due to the presence of SPIONs and could even be applied in real time monitoring in addition to the drug delivery platform (meaning theranostic nanoparticles). It was confirmed in previous studies that SPIONs produced negative contrast in MR imaging by reducing T2 relaxation time. , …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These results indicated that the synthesized nanoparticles have imaging capability due to the presence of SPIONs and could even be applied in real time monitoring in addition to the drug delivery platform (meaning theranostic nanoparticles). It was confirmed in previous studies that SPIONs produced negative contrast in MR imaging by reducing T2 relaxation time. , …”
Section: Discussionsupporting
confidence: 73%
“…It was confirmed in previous studies that SPIONs produced negative contrast in MR imaging by reducing T2 relaxation time. 43,44 According to the ICP-OES results, the highest uptake rate of TMZ-loaded nanoparticles with or without FA and with or without MF at different times occurred in the spleen, liver, heart, kidneys, and ultimately the brain (healthy and tumor tissues, Figure 7). Similar results have also been reported for nanoparticles modified with FA and magnetic nanoparticle, respectively, by Li et al and Chertok et al, indicating that folic acid ligands or magnetic field has no significant effect on the uptake of other organs except the brain.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Khoei et al . reported an investigation on the uptake and cytotoxic effect of polycaprolactone/chitosan/nanographene oxide coated on Fe 3 O 4 MNPs as a carrier for 5-FU, and then studied radiofrequency hyperthermia, using the alternate magnetic field on proliferation capacity of CT26 colon cancer cell [ 99 ]. The dialysis bag method was used to measure the 5-FU drug release from functionalized MNPs, and it resulted in enhanced cellular uptake with elevated MNPs concentrations.…”
Section: Main Textmentioning
confidence: 99%
“…GO exhibits a p-conjugated structure, where efficient loading of drugs onto GO nano sheets occurs by π-π stacking and van de Waals forces [4] . GO has been used as an excellent nanocarrier for various model drugs, for example ibuprofen and amoxicillin [14] , heparin [15] , 5-fluorouracil [16] , and doxorubicin [17] .…”
Section: Introductionmentioning
confidence: 99%